2012
DOI: 10.1186/1471-2407-12-4
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1 activation induces doxorubicin resistance in MCF7 3-D spheroids via P-glycoprotein expression: a potential model of the chemo-resistance of invasive micropapillary carcinoma of the breast

Abstract: BackgroundInvasive micropapillary carcinoma (IMPC) of the breast is a distinct and aggressive variant of luminal type B breast cancer that does not respond to neoadjuvant chemotherapy. It is characterized by small pseudopapillary clusters of cancer cells with inverted cell polarity. To investigate whether hypoxia-inducible factor-1 (HIF-1) activation may be related to the drug resistance described in this tumor, we used MCF7 cancer cells cultured as 3-D spheroids, which morphologically simulate IMPC cell clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
122
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(133 citation statements)
references
References 48 publications
1
122
1
2
Order By: Relevance
“…One highly studied ABC transporter protein is P-glycoprotein (Pgp) (an MDR1 gene product) that has been linked to MDR in cancer cells [110]. High levels of Pgp are found in MDR cells and coincide with higher expression of HIF-1 [111][112][113]. Doublier and co-workers found MCF7 breast cancer cells grown under hypoxia to be resistant to doxorubicin.…”
Section: Consequences For Drug Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…One highly studied ABC transporter protein is P-glycoprotein (Pgp) (an MDR1 gene product) that has been linked to MDR in cancer cells [110]. High levels of Pgp are found in MDR cells and coincide with higher expression of HIF-1 [111][112][113]. Doublier and co-workers found MCF7 breast cancer cells grown under hypoxia to be resistant to doxorubicin.…”
Section: Consequences For Drug Developmentmentioning
confidence: 99%
“…They also observed that the binding of HIF-1 to the MDR1 gene promoter was higher in hypoxic cells. These cells accumulated lower levels of doxorubicin compared to normoxic cells [112]. Therefore, these roles of HIF-1 should be assessed during optimization of treatment strategies.…”
Section: Consequences For Drug Developmentmentioning
confidence: 99%
“…HIF-1α is involved in a wide range of biological functions, such as angiogenesis, cell proliferation, and cell survival, as well as vascular remodeling (4)(5)(6). Studies have suggested that the stroma of most human tumors expresses HIF-1α, which may be involved in regulating the expression of the downstream vascular endothelial growth factor (VEGF) gene, and be related to tumor angiogenesis and tumor cell migration (7,8).…”
mentioning
confidence: 99%
“…Not only does it influence all tumor features, but it also enables tumor cells to acquire an aggressive phenotype and ultimate resistance to chemotherapy and radiotherapy (11,21) . Several papers have described some cell hypoxia drawbacks such as poor drug delivery, namely cetuximab and transtuzumab on immunotherapy (19) , the impaired cellular uptake of many drugs caused by tumor associated acidity (9) , as well as the role of key-cascade hypoxia molecules in therapeutics (17) .…”
Section: Introductionmentioning
confidence: 99%